Hacked Aqedah: Genesis 22 in dialogue with contemporary political Science Fiction - Uhlenbruch, Frauke (The journal of Hebrew scriptures, 2016)
The present issue is a collection of essays which were originally presented as conference papers at the “Science Fiction and the Bible” unit of the European Association of Biblical Studies in Leipzig (2013) and Vienna (2014). It includes an introduction by the editor, Frauke Uhlenbruch, as well as a response by James F. McGrath.